Make way for ducklings - McCloskey, Robert (New York: Scholastic, 1969)
The busy Boston streets are too dangerous for eight little ducklings. But with the help from a friendly policeman, Mrs. Mallard and her family arrive safely at their new home.
Keywords: Ducks -- Fiction; Boston (Mass.) -- Ma. -- fiction